Approximations of the solution of a stochastic Ginzburg-Landau equation - BRECKNER, Brigitte E.; LISEI, Hannelore (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
This paper presents a method to approximate the solution of a stochastic Ginzburg-Landau equation with multiplicative noise term. Error estimates for the approximation of the solution are given. Mathematics Subject Classification (2010): 60H15, 34K28, 35Q56.